2015
DOI: 10.3923/ajb.2015.267.280
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Molybdenum Induced Alteration in Oxidative Indices, Biochemical Parameters and Sperm Quality in Testis of Wistar Male Rats

Abstract: The present study was carried out to investigate the effects of ammonium molybdate on lipid peroxidation, antioxidant, biochemical and semen parameters in male Wistar rats. Group I served as control while group II, III and IV received 50, 100 and 150 mg kgG for 60 days and thereafter left for recovery study for 60 days. The present study examined the effects of ammonium molybdate on serum testosterone, Follicle Stimulating Hormone (FSH) and Luteinizing Hormone (LH) along with sperm parameters. Estimations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…Thus, the observed reduction in the testicular protein content in DEX control rats could be attributed to disturbances in protein metabolism due to DEX‐induced testicular injury and could impair maturation of sperm. A similar decline in testicular protein content has been reported by Pandey & Jain () who stated that ammonium molybdate administration causes a significant decline in testicular protein level. The restoration of the testicular protein content after GSE administration could improve sperm maturation, which shows the androgenic potential of the extract.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the observed reduction in the testicular protein content in DEX control rats could be attributed to disturbances in protein metabolism due to DEX‐induced testicular injury and could impair maturation of sperm. A similar decline in testicular protein content has been reported by Pandey & Jain () who stated that ammonium molybdate administration causes a significant decline in testicular protein level. The restoration of the testicular protein content after GSE administration could improve sperm maturation, which shows the androgenic potential of the extract.…”
Section: Discussionsupporting
confidence: 86%
“…The results exhibited a significant drop in the serum level of testosterone in CB10 and CB40 groups than in the control group. This decrease was dose-dependent, agreeing with Pandey and Jain 64 findings. Meeker et al 65 showed a decline in testosterone levels after Mo exposure in a case study.…”
Section: Discussionsupporting
confidence: 91%
“…Meeker et al 65 showed a decline in testosterone levels after Mo exposure in a case study. The decline in testosterone levels in the rats nourished on CB fertilized by MoO 3 -NPs could be attributed to a reduction in the pituitary LH secretion or underutilization of cholesterol in testosterone synthesis 64 . Increased oxidative stress could potentially affect the Leydig cells' ability to operate normally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysosomal enzyme ACP is a biomarker of spermatogenesis steps mediated by androgenic influence 34 . Likewise, Alp is correlated with plasma membrane permeability and germ cell biomarkers in the cell 35 . The compromised plasma membrane integrity due to lipid peroxidation may have caused leakage of the enzyme resulting in the reduced activity of the enzymes.…”
Section: Discussionmentioning
confidence: 99%